2016
DOI: 10.1172/jci85097
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell dysfunction and diabetic sensory neuropathy in the cornea

Abstract: Diabetic peripheral neuropathy (DPN) often leads to neurotrophic ulcerations in the cornea and skin; however, the underlying cellular mechanisms of this complication are poorly understood. Here, we used post-wound corneal sensory degeneration and regeneration as a model and tested the hypothesis that diabetes adversely affects DC populations and infiltration, resulting in disrupted DC-nerve communication and DPN. In streptozotocin-induced type 1 diabetic mice, there was a substantial reduction in sensory nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 65 publications
2
75
1
Order By: Relevance
“…The round-shaped cells observed in the resting corneas expressed CD86, suggesting they are phenotypically mature and/or activated. Our study revealed the presence of DCs along each vertical fiber that crosses the BM and branches into epithelial nerve endings, suggesting a potential role of residential DCs for epithelium innervation by not only releasing neurotrophic factors, such as CNTF39, but also by maintaining direct contact with the nerve as it passes through the BM. This should have implications in our understanding of the immune-nervous interplay in maintaining tissue homeostasis and in corneal response to injury and infection40.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The round-shaped cells observed in the resting corneas expressed CD86, suggesting they are phenotypically mature and/or activated. Our study revealed the presence of DCs along each vertical fiber that crosses the BM and branches into epithelial nerve endings, suggesting a potential role of residential DCs for epithelium innervation by not only releasing neurotrophic factors, such as CNTF39, but also by maintaining direct contact with the nerve as it passes through the BM. This should have implications in our understanding of the immune-nervous interplay in maintaining tissue homeostasis and in corneal response to injury and infection40.…”
Section: Discussionmentioning
confidence: 67%
“…In the cornea, the transcription of NGF, NT-3, and BDNF was detected in ex vivo human corneas44 while others have shown that NGF was primarily expressed in the limbal epithelial cells45. In the accompanied study39, we showed that the intraepithelial DCs express CNTF, a factor known to promote sensory neuron survival and exon regeneration464748, and that in wounded corneas, all CD11c and HMC-2 positive cells are round-shaped. More interestingly, we showed that DC depletion not only delayed epithelial wound closure26 but also adversely affected sensory nerve regeneration in wounded corneas.…”
Section: Discussionmentioning
confidence: 71%
“…In both diabetic patients and animal models, the most severe reduction in nerve fiber and branch density occur in the sub-basal nerve plexus close to the corneal epithelium, possibly explaining the correlation between diabetic keratopathy and corneal neuropathy (De Cillà et al, 2009; He and Bazan, 2012; Wang et al, 2012; Zhivov et al, 2013; Cai et al, 2014; Davidson et al, 2014; Stem et al, 2014). Upon corneal epithelial wounding, severed subbasal nerves regenerate significantly slower in diabetic than in non-diabetic animals (Wang et al, 2012; Gao et al, 2016). The sub-basal nerve alterations in diabetic mice are accompanied by abnormalities of dendritic cells that may serve neurotrophic functions (Leppin et al, 2014; Gao et al, 2016).…”
Section: General Manifestations Of Diabetes In the Corneamentioning
confidence: 98%
“…Upon corneal epithelial wounding, severed subbasal nerves regenerate significantly slower in diabetic than in non-diabetic animals (Wang et al, 2012; Gao et al, 2016). The sub-basal nerve alterations in diabetic mice are accompanied by abnormalities of dendritic cells that may serve neurotrophic functions (Leppin et al, 2014; Gao et al, 2016). Several studies have documented corneal neuropathy early in diabetes, before the development of DR (Zhivov et al, 2013; Papanas and Ziegler, 2013; Petropoulos et al, 2015; Szalai et al, 2016).…”
Section: General Manifestations Of Diabetes In the Corneamentioning
confidence: 98%
See 1 more Smart Citation